A spatial analysis of woodfuel based on WISDOM GIS methodology: Multiscale approach in Northern Spain. (15th April 2015) - Sánchez-García, Sandra; Canga, Elena; Tolosana, Eduardo; Majada, Juan
Highlights: A multiscale GIS analysis of woodfuel supply/demand. Template for scale or scenario dependant integration of data into WISDOM methodology. Pixel level calculation of all data enables operations between rasterized maps. Shows benefits of analytical GIS tools in bioenergy system management and planning. Abstract: Given the complexity of generating energy from biomass, the need has arisen for support tools to assist in balancing energy and forestry policies which are sufficiently flexible to address the issues of planning and management at small and large scales. The present study aims to adapt WISDOM GIS methodology for application in the autonomous region of Asturias (Northern Spain) and thereby, by creating a geodatabase, to contribute to a support tool for investigating the potential of woodfuel. This will aid the public administration by providing information on woodfuel supply and demand at the regional, municipality and site-specific level, and thus assist in decision making in terms of formulating new energy strategies. In terms of supply (t year − 1 ), in this work, woodfuel from forest area is defined as the crown fraction only (branches and leaves), although in the case of Eucalyptus spp., bark is also included as it is remains on-site following extraction of eucalypts for the pulp industry. Non-Forest Direct Supply was calculated on the basis of the relevant categories from an agricultural land use inventory and average woodfuel productivity. In addition, physical and legal constraints related to accessibility of the woodfuel were considered, the former applying restriction filters with values weighted depending on the interaction between slope map, road networks and centres of population, and the latter considering legal limitations in protected areas. In addition, unused waste from the wood processing industry was included. To calculate total woodfuel demand (t year − 1 ) for energy generation (heat and electricity), both the residential and industrial sector were taken into account. All data was georeferenced through Geographic Information Systems (GISs), which allow operations between raster maps to be performed to generate numeric and spatial results focusing on logistics and biomass strategies, depending on the inputs data and scale employed for each scenario considered. In addition, the application of the methodology at the site-specific level illustrates the practical implementation at the small scale of the geodatabase created, by evaluating the woodfuel available to feed, in case 1, a wood-fired power plant in a specific proposed location and, in case 2, this plant combined with a second plant in a different municipality, both cases also taking into consideration industrial demand.